SEJARAH PERKEMBANGAN KURIKULUM PAI DI INDONESIA DARI TAHUN 1947 SAMPAI 2013 - Fuziawati, Elit (LPPM STAI Al-Azhary Cianjur, 2024)
This research discusses the development of the curriculum in Indonesia from the post-independence era to the 2013 Curriculum. The curriculum, as a guide in the education system, plays a crucial role in achieving learning objectives at both the primary and secondary levels. The curriculum changes throughout the history of Indonesian education aim to align with the demands of the times, social changes, and technological advancements. Although the curriculum has undergone improvements, the main challenges remain in its implementation, particularly in terms of teacher preparedness and uneven educational infrastructure. This study also identifies that, despite the introduction of curricula such as the 1947, 1952, 1964, and 2013 Curricula, their application often faces obstacles in practice, especially in integrating theory with practice. Therefore, regular evaluation and adjustments to the curriculum are essential to ensure the education system remains relevant to global developments and societal needs.